The enduring coloniality of ecological modernization: Wind energy development in occupied Western Sahara and the occupied Syrian Golan Heights. (May 2023) - Alkhalili, Noura; Dajani, Muna; Mahmoud, Yahia
Abstract: The dominant narratives on how to confront climate change are often presented as neutral proposals concerned with the well-being of the planet and its inhabitants. The main objective of this article is to exemplify how concepts like Ecological Modernization and Sustainable Development are used in the name of energy transitions to prolong illegal military occupations in two territories, namely occupied Western Sahara and the occupied Syrian Golan Heights. By combining first-hand and secondary data from our cases, we also expose the enduring coloniality of such concepts that have been critiqued not only for their lack of neutrality but also for their contribution to the denial of basic human rights such as self-determination, sovereignty, and the right to resourcehood. We argue that renewable energy projects, in the two settings studied, are a manifestation of an ecological modernization that ignores aspects of justice and self-determination. Although touted as a solution to mitigating climate change, wind energy development in these two cases violates international law and the principle of self-determination.